Impact of AI and tech-driven solutions in hospitality and tourism - Kumar, Sanjeev; Talukder, Mohammad Badruddoza 1985-; Tyagi, Pankaj Kumar 1979- (IGI Global, 2024)
With today's rapidly evolving digital landscape, businesses in the hospitality and tourism industries face the challenge of harnessing the power of emerging technologies to stay competitive and meet the evolving needs of travelers. From personalized guest experiences to efficient operations and sustainable practices, there is a growing demand for innovative solutions that leverage artificial intelligence (AI) and cutting-edge technology. However, navigating this technological landscape can be daunting, with businesses often grappling with questions of implementation, integration, and ethical considerations. Impact of AI and Tech-Driven Solutions in Hospitality and Tourism emerges to provide insight and guidance in addressing these challenges. By delving into the transformative potential of AI and technology, this book offers a comprehensive exploration of how these innovations are reshaping the hospitality and tourism sectors. Through in-depth analyses, case studies, and practical examples, readers gain valuable insights into the myriad ways in which AI-driven solutions can enhance guest experiences, streamline operations, and drive sustainable practices within the industry
Keywords: Artificial intelligence -- Industrial applications; Hospitality industry -- Data processing; Hotel management -- Data processing; Information storage and retrieval systems -- Tourist trade; Tourism -- Data processing